2006
DOI: 10.1111/j.1742-1241.2006.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline: a new glycylcycline antimicrobial

Abstract: Tigecycline is a new glycyclcycline antimicrobial recently approved for use in the USA, Europe and elsewhere. While related to the tetracyclines, tigecycline overcomes many of the mechanisms responsible for resistance to this class. It demonstrates favourable in vitro potency against a variety of aerobic and anaerobic Gram-positive and Gram-negative pathogens, including those frequently demonstrating resistance to multiple classes of antimicrobials. This includes methicillin-resistant Staphylococcus aureus, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 79 publications
0
24
0
1
Order By: Relevance
“…The drug demonstrated a limited activity, similar to other tetracyclines, only against P. aeruginosa. Other authors reported such a restricted activity also against Proteus mirabilis [8,13,26,[41][42][43] : the AcrAB transport system appears to be associated with the intrinsically reduced susceptibility to tigecycline in this microorganism [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The drug demonstrated a limited activity, similar to other tetracyclines, only against P. aeruginosa. Other authors reported such a restricted activity also against Proteus mirabilis [8,13,26,[41][42][43] : the AcrAB transport system appears to be associated with the intrinsically reduced susceptibility to tigecycline in this microorganism [10] .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe hepatic impairment (Child-Pugh class C) the systemic clearance of tigecycline is decreased by approximately 55%, and the elimination t 1/2 is prolonged by approximately 43% compared to healthy subjects [33]. In patients with moderate hepatic impairment (Child-Pugh class B) the systemic clearance of tigecycline decreases by nearly 25% compared to healthy subjects [34].…”
Section: Non-enzymatic Degradation Into Epimermentioning
confidence: 98%
“…2,4 Uma única restrição a estas drogas refere-se às mulheres grávidas e crianças em fase de crescimento, uma vez que tetraciclinas são depositadas nos ossos e dentes durante a calcificação, o que pode levar a um descoloramento dos dentes e a uma inibição do crescimento ósseo em crianças. 55 Outros efeitos menos comuns são fotossensibilidade, que é caracterizada pelo aparecimento de manchas tipo queimadura de sol na pele, urticária, dor de cabeça, dor abdominal, hipertensão, febre, leucopenia leve, anemia, trombocitopenia. 4 Tetraciclinas são fortes agentes quelantes e as suas propriedades antibacterianas e farmacocinéticas são afetadas pela coordenação de íons metálicos presentes no meio biológico.…”
Section: Efeitos Adversos E Interação Com Outras Drogasunclassified